GCM2 p.Tyr394Ser variant in Ashkenazi Israeli patients with suspected familial isolated hyperparathyroidism - Szalat, Auryan; Shpitzen, Shoshana; Pollack, Rena; Mazeh, Haggi; Durst, Ronen; Meiner, Vardiella (Frontiers in Endocrinology, 2023)
Context: A germline mutation may be identified in up to 10% of primary hyperparathyroidism (PHPT) patients. In 2017, a high frequency of the GCM2 [(NM_ 004752.4) c.1181A>C; p.Tyr394Ser; rs142287570] variant was reported in PHPT Ashkenazi Jews (AJ). Objective: To evaluate the presence of the GCM2 p.Tyr394Ser variant in PHPT Israeli patients addressed for genetic evaluation to characterize their phenotype and clinical management. Method: Patients with PHPT addressed for genetic screening because of suspected familial hypocalciuric hypercalcemia (FHH), family history of isolated hyperparathyroidism (FIHP) or failed parathyroidectomy with persistent PHPT were recruited. Those with normal initial selected genes sequencing or Hyperparathyroid genetic panel, completed a GCM2 p.Tyr394Ser variant sequencing. The prevalence of the variant was also evaluated at our local genomic database. Results: 42 single individuals from non-related kindreds were evaluated. A disease-causing mutation was found in 11 (26.1%): 10 were diagnosed with FHH (8 CASR and 2 AP2S1 mutations); one patient had a CKN2B mutation. In 28 of the remaining patients, GCM2 p.Tyr394Ser variant was positive in 3 (10.7%), all were AJ. Within AJ (15/28, 53.5%), the rate of p.Tyr394Ser variant was 3/15 (20%), and of those, two had a history of familial isolated hyperparathyroidism.Multi-glandular parathyroid adenoma/hyperplasia was also observed in 2 of these patients. No clinical or laboratory findings could discriminate patients with the GCM2 p.Tyr394Ser variant from patients with FHH. Cinacalcet normalized calcium levels in one patient. The prevalence of the GCM2 p.Tyr394Ser variant in 15407 tests at our local genomic database was 0.98%. Conclusions: In contrast to previous observations, GCM2 p.Tyr394Ser variant associated phenotype may be mild in AJ with FIHP,